Implementation considerations for non-communicable disease-related integration in primary health care: a rapid review of qualitative evidence - N. Leon; H. Xu (BMC, 2023)
Abstract Background Integrated delivery of primary health care (PHC) services is a health reform recommended for achieving ambitious targets of the Sustainable Development Goals and Universal Health Coverage, responding to growing challenges of managing non-communicable and multimorbidity. However, more evidence is needed on effective implementation of PHC integration in different country settings. Objective This rapid review synthesized qualitative evidence on implementation factors affecting integration of non-communicable disease (NCD) into PHC, from the perspective of implementers. The review contributes evidence to inform the World Health Organizations' guidance on integration of NCD control and prevention to strengthen health systems. Method The review was guided by standard methods for conducting rapid systematic reviews. Data analysis was guided by the SURE and WHO health system building blocks frameworks. We used Confidence in the Evidence of Reviews of Qualitative Research (GRADE-CERQual) to assess the confidence of the main findings. Results The review identified 81 records eligible for inclusion, from 595 records screened. We sampled 20 studies for analysis (including 3 from expert recommendations). Studies covered a wide range of countries (27 countries from 6 continents), the majority from low-and middle-income countries (LMICs), with a diverse set of NCD-related PHC integration combinations and implementation strategies. The main findings were categorised into three overarching themes and several sub-themes. These are, A: Policy alignment and governance, B: Health systems readiness, intervention compatibility and leadership, and C: Human resource management, development, and support. The three overarching findings were assessed as each having a moderate level of confidence. Conclusion The review findings present insights on how health workers responses may be shaped by the complex interaction of individual, social, and organizational factors that may be specific to the context of the intervention, the importance of cross-cutting influences such as policy alignment, supportive leadership and health systems constraints, knowledge that can inform the development of future implementation strategies and implementation research.